2016
DOI: 10.1159/000444022
|View full text |Cite
|
Sign up to set email alerts
|

Protection on Skin Aging Mediated by Antiapoptosis Effects of the Water Lily (<b><i>Nymphaea Tetragona</i></b> Georgi) via Reactive Oxygen Species Scavenging in Human Epidermal Keratinocytes

Abstract: Aims: The water lily (WL) is found in Europe, Asia, and North America. WL reportedly has various pharmacological activities that improve the activities of daily life in humans. To our knowledge, no previous study has investigated about the aspect of protection on skin aging due to the mitochondria-mediated antiapoptosis effects of WL rhizome extract (WLRE) on human epidermal keratinocytes. Methods: Human epidermal keratinocytes cells were treated with WLRE (100, 200, and 400 μg/ml) for 1 h and then with ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Furthermore, biliverdin can be converted by the enzyme biliverdin reductase into bilirubin, a potent antioxidant, capable of protecting cells from 10,000-fold higher concentrations of H 2 O 2 ( (Morse , Choi, 2005)). Activation of HO-1 was described already as a possible mechanism by which different natural compounds delay skin aging (Park et al, 2016).…”
Section: Ros Mitochondrial Dna and Agingmentioning
confidence: 99%
“…Furthermore, biliverdin can be converted by the enzyme biliverdin reductase into bilirubin, a potent antioxidant, capable of protecting cells from 10,000-fold higher concentrations of H 2 O 2 ( (Morse , Choi, 2005)). Activation of HO-1 was described already as a possible mechanism by which different natural compounds delay skin aging (Park et al, 2016).…”
Section: Ros Mitochondrial Dna and Agingmentioning
confidence: 99%
“…Similarly, other natural extracts, such as those from Nymphaea tetragona Georgi and Schisandra chinensis (Turcz.) Baill (from which deoxyschisandrin was isolated), have been shown to possess ROS scavenging antioxidant properties (Park et al 2016;Hou et al 2015). When ROS generation and antioxidant capacity are in relative balance, the expression of specific nuclear genes can be modulated to maintain the energy metabolism necessary for the cell's survival.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ROS generation is considered to be an additional critical mediator in triggering the apoptotic machinery (Ichihashi et al 2003). Recent studies demonstrated that ROS may cause oxidative damage to the DNA, RNA, proteins, and lipids of affected cells and induce apoptosis through the induction of mitochondrial membrane permeability transition and the release of pro-apoptotic proteins when ROS levels exceed a certain threshold (Park et al 2016;Ueda et al 2002;Maraldi et al 2009). In brief, excessive ROS levels downregulate anti-apoptotic proteins and upregulate pro-apoptotic proteins, resulting in interference with the normal release of cytochrome-c, which activates the caspase family proteins, and finally induces cell death (Ryu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values indicate 50% decrease of ABTS radical. DPPH radical 소거능의 경우에는 유리라디칼이 소거되어지 는 것을 이용하는 반면, ABTS radical 소거능은 양이온인 라디 칼이 소거되어지는 것을 이용한다 [28]. 부평초의 용매별 추출 물의 ABTS radical 소거능을 비교한 결과는 Table 2와 같다.…”
unclassified